Interactive Macromedia Flash–Based Learning Media for K3LH Instruction in Vocational Electronics Education - Mutia Fatila; Ilmiyati Rahmy Jasril; Firas Tayseer Ayasrah (Sagamedia Teknologi Nusantara, 2026)
This study developed interactive learning media using Macromedia Flash to enhance Occupational Health, Safety, and Environmental Awareness (K3LH) instruction within the Basic Electronics curriculum in vocational high schools. The research employed a Research and Development approach guided by the 4D model (Define, Design, Develop, and Disseminate) to produce a validated multimedia learning product aligned with the Merdeka Curriculum. During the Define stage, needs assessment and learner analysis revealed low student engagement and conceptual difficulties with electronics safety topics, underscoring the need for technology-based instructional innovation. The designed media integrated text, visuals, animations, audio, and interactive assessments to support autonomous and student-centred learning. Expert validation involving material and media specialists resulted in high validity scores of 94.7% and 94.8%, indicating strong curriculum alignment, conceptual clarity, interface organisation, and language quality. Field testing with Grade 10 Electronics Engineering students yielded a practicality score of 85.1%, confirming that the media was easy to operate, pedagogically relevant, visually engaging, and effective in supporting understanding and participation. These outcomes demonstrate that Macromedia Flash-based learning media remain highly functional for vocational classroom environments, particularly where technological infrastructure is limited. The study concludes that the developed media can serve as a robust instructional tool to strengthen student motivation, improve comprehension of K3LH concepts, and enrich technology-enhanced learning in vocational electronics education. Future research is recommended to expand implementation across different school contexts and migrate the product to modern digital platforms to improve scalability and accessibility.